2006
DOI: 10.1159/000095613
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Round Window and Cochleostomy Approaches with a Prototype Hearing Preservation Electrode

Abstract: Introduction: Preservation of residual hearing in cochlear implant recipients has been demonstrated to be possible and provides the potential benefit of combined electric and acoustic auditory stimulation. A prototype 16-mm multichannel array has been designed to facilitate placement of 22 electrodes without damage to intracochlear structures. The electrode array is suitable for insertion via the round window membrane (RWM) or a small cochleostomy. Aim: To evaluate the insertion trajectory and the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
131
1
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(138 citation statements)
references
References 31 publications
2
131
1
4
Order By: Relevance
“…To maximize the flexibility in programming, most of these EAS electrodes retain the same number of stimulating contacts found in the corresponding standard length electrodes in regular cochlear implants. Temporal bone studies using these shortened electrodes indicate that they can be introduced without damage and human trials have shown that subjects implanted with these electrodes experience a smaller average increase in acoustic threshold than is seen with full length electrodes in similar subject populations [134][135][136][137].…”
Section: ) Standard Arrays-the Advanced Bionics Hifocus Helix™ and mentioning
confidence: 99%
“…To maximize the flexibility in programming, most of these EAS electrodes retain the same number of stimulating contacts found in the corresponding standard length electrodes in regular cochlear implants. Temporal bone studies using these shortened electrodes indicate that they can be introduced without damage and human trials have shown that subjects implanted with these electrodes experience a smaller average increase in acoustic threshold than is seen with full length electrodes in similar subject populations [134][135][136][137].…”
Section: ) Standard Arrays-the Advanced Bionics Hifocus Helix™ and mentioning
confidence: 99%
“…The drilling required occurs very close to the chorda tympani-facial nerve angle, thus putting both nerves at risk. Although this should be possible with a thorough knowledge of anatomy, the same author has stated that many CI surgeons are not confident enough to perform complete facial recess dissection [13] . On the other hand, there is much evidence that an anterior cochleostomy can result in scala media or vestibuli insertions [14] .…”
Section: Synopsis Of Key/new Findingsmentioning
confidence: 99%
“…Within this study, comparisons between long-term Hybrid-S users and long-term long array users who were matched on word understanding in quiet showed a difference in speech perception in noise (using both multi-talker babble and steady-state noise), suggesting that the Hybrid-S users perform better within a more realistic listening environment. Despite these benefits, Briggs and colleagues (Briggs et al, 2006) identified the possibility that shortening of the electrode array to 10mm may cause a place-frequency mismatch because only the basal portion of the cochlea will be stimulated, causing a disproportionately higher frequency percept than with a standard array. Further, should hearing not be preserved, then concerns have been raised that speech perception outcomes will be impaired for individuals who only receive electrical stimulation in such a limited region of the cochlea (Gstoettner et al, 2009).…”
Section: Effect Of Residual Hearing Preservation On Music Perception mentioning
confidence: 99%